Epistemologi Pendidikan Agama Islam: (Konstruksi Pengetahuan dan Metodologi Pengetahuan) - Abdul Muqtadir. S; Tobroni Tobroni (Ikhlas : Jurnal Ilmiah Pendidikan Islam, 2025)
This study examines the construction and methodology of knowledge in the scope of Islamic Religious Education (PAI). This study explores five main aspects: (a) Sources of knowledge in Islamic Religious Education, (b) Scientific paradigms between revelation and reason, (c) Integrative research methodology in Islamic studies, (d) Deconstruction of the boundaries of scientific disciplines in Islamic Religious Education, and (e) Episteme of contemporary Islamic knowledge: between tradition and modernity. With this approach, Islamic Religious Education can continue to develop, be understood, and practiced in the life of society, so that a harmonious and orderly order of life is created. The study of concepts in the scope of Islamic Religious Education (PAI) must continue to be developed along with the emergence of complex problems amidst the development of globalization, as a basis for contemporary studies. This study is expected to be a reference for educators and education practitioners in developing more effective and relevant Islamic Religious Education (PAI) materials.